PENGARUH PERTUMBUHAN EKONOMI DAN INFLASI TERHADAP TINGKAT PENGANGGURAN DI INDONESIA - Warhamni; Fitri Meilani; Lailatul Husni; Warzukni; Sri Kurniah Wulandari; Marina; Muhammad Hafis; Jolianis (STKIP Subang, 2026)
This study aims to analyze the effect of economic growth and inflation on the unemployment rate in Indonesia. The research used a quantitative method with an associative approach and secondary data from 1960–2024 obtained from the Central Statistics Agency (BPS). Data analysis was conducted using multiple linear regression. The results showed that partially, economic growth and inflation did not have a significant effect on the unemployment rate. Simultaneously, both variables also did not have a significant influence on unemployment in Indonesia. The coefficient of determination value of 0.05 indicates that only 5% of unemployment variation can be explained by economic growth and inflation, while the remaining 95% is influenced by other factors outside the research model, such as the quality of human resources, investment, education, and employment opportunities.